Molecular detection and genotyping of pathogenic protozoan parasites in raw and treated water samples from southwest Colombia (2018)
Background: Protozoan parasites such as Giardia duodenalis, Cryptosporidium spp., Cyclospora cayetanensis, Toxoplasma gondii and Entamoeba histolytica represent a great challenge to the systems producing water for human consumption because their cystic forms are persistent in the environment and resist to the disinfection methods conventionally used for their control. In this study, we investigated the presence of these protozoan pathogens in both raw and treated water samples used for the production of drinking water in Nariño Department, southwest Colombia. We collected 110 water samples (10 lof each sample) and analyzed them with real-time PCR (qPCR). qPCR-positive samples were genotyped with PCR and DNA sequencing. Results: Giardia duodenalis was detected in 35/110 (31.8%) of the samples and Cryptosporidium spp. in 9/110 (8.2%) of the samples; no sample was positive for T. gondii, E. histolytica or C. cayetanensis. Giardia duodenalis was detected in samples of both raw water (Drinking Water Treatment Plants (DWTP): 47.83%;Drinking Water Rural Plants (DWRP): 18.42%) and water collected either after conventional physicochemical treatment (26.09%) or after disinfection by chlorine (50%), whereas Cryptosporidium spp. were only detected in raw waters (DWTP: 17.39%; DWRP: 13.16%). The two pathogens were detected in both types of treatment plants supplying water to urban areas and to rural zones. Analysis of gdh and tpi markers identified assemblages AI, AII and H of G. duodenalis, while analysis of the small subunit rRNA and gp60 markers of Cryptosporidium-positive samples identified C. parvum (Subtype IIcA5G3c), C. galli, C. molnari, Cryptosporidium sp. genotype II of bats and Cryptosporidium sp. genotype VIII of birds. Conclusions: The results obtained demonstrate the presence of protozoan parasites in the water of the study region, and the need to improve the surveillance systems for these pathogens and identify the corresponding sources of contamination. © 2018 The Author(s).